The Influence Of The Development Of Artificial Intelligence Technology In The Industrial Field - Shariar Calabria Islam Taufik; Rismayanti Rismayanti; Dylan Revina Sopian; Advensius Agung Dede Saputra (Jurnal Indonesia Sosial Teknologi, 2023)
Artificial Intelligence (AI) has become a significant development of information and communication technology in the last ten years. However, its implementation in Indonesia is still relatively low due to constraints on worker skills and insufficient infrastructure investment. Nonetheless, AI has the potential to improve business performance, such as in the use of cloud computing. The application of AI in the industry requires changes and adjustments to technological developments. The use of AI is significantly affecting various sectors and people's lifestyles, and governments have an important role to play in providing technology-based services. The purpose of this study is to examine the influence of AI in the industrial sector, understand its development in Indonesia, and analyze the positive and negative impacts of using AI in the future. This study uses a descriptive method combined with qualitative content analysis techniques and field reviews. The descriptive method is a research method that aims to obtain an objective picture of the situation. Thus, the implementation of AI in Indonesia still needs to be improved by overcoming skills and investment constraints. Governments should play an active role in supporting the development of AI in the industry while considering its positive and negative impacts in the future